FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN KEDAI KOPI MODERN DI BONDOWOSO - Mochamad Hafezd As'ad; Joni Murti Mulyo Aji (University of Jember, 2020)
In the modern era today, coffee consumption lifestyle started to develop and penetrated the community especially in urban areas. The rapid growth of coffee shops in Indonesia, could be seen as well in Bondowoso. The existence of city branding